The potential of COPCA's coaching for families with infants with special needs in low- and middle-income countries - Akhbari Ziegler, Schirin; de Souza Morais, Rosane Luzia; Magalhães, Lívia; Hadders-Algra, Mijna (Frontiers in Pediatrics, 2023)
Infants at high biological risk of or with a neurodevelopmental disorder run a high risk of delayed school readiness. This is especially true for infants in low- and middle-income countries (LMICs). This perspective paper first summarizes evidence on intervention elements that are effective in promoting family well-being and child development in infants at high biological risk in high income countries. Crucial elements are family centeredness, goal orientation, a home setting, focus on activity and participation, and challenging the infant to explore the world and the own body by means of self-produced movements. The studies revealed that coaching as applied in COPCA (COPing and CAring for infants with special needs) is a pivotal element determining the success of intervention. The paper continues by describing COPCA and its coaching. Next, we report on two pilot studies addressing COPCA’s implementation in Brazil. Finally, we discuss why COPCA is a promising early intervention program for infants at high biological risk of neurodisability in LMICs: COPCA is adapted to the families’ strengths and needs, it empowers families and promotes child development therewith facilitating school readiness. Moreover, it may be delivered by tele-coaching therewith eliminating families’ burden to travel to distant intervention clinics.